Efecto de dos niveles de fertilización nitrogenada en el desarrollo inicial de Cordia Alliodora r. & p. oken (laurel) en el Cantón Jipijapa año 2016. Propuesta de difusión tecnológica - Indacochea Merchán, Carlos (2016)
In the enclosure the Palmital, of the Jipijapa canton, Manabí province, a fertilization rehearsal settled down, with three types of nitrogen fertilizers and two-application dose, in a recently established plantation of (Cordia alliodora R. & P. Oken) laurel The objective was to evaluate the effect of two levels of nitrogen fertilization in the initial development of "laurel". The experiment was established in factorial arrangement 3 (types of fertilizers) x 2 (application dose), on a design of Blocks at random, with three repetitions. The total area of each parcel was of 180 m2 (12 m x 15 m) and the laurel was planted at a distance of 3 m x 3 m. Each parcel was conform by 20 laurel plants, of which the 6 plants of the center of the parcel were evaluated. The results, to the three months of the first application of the fertilizers, demonstrated that the simple effect of the types of fertilizers was significant only for the number of leaves, but it does not stop the other evaluated variables. The simple effect of the doses did not present significant differences, for none of the studied variables. However, by means of the orthogonal comparisons, it was found that the treatments with fertilizers presented better results that the witness, also, the Urea was better than the witness. But there were not significant differences among the doses. These results although they are not definitive, due to the short period of evaluation, they suggest that the laurel responds well to the nitrogen fertilization to the beginning of the establishment.